The Matthean Jesus’ surprising instruction to obey the teachers of the Law and Pharisees - Francois P. Viljoen (HTS Teologiese Studies/Theological Studies, 2018)
Jesus’ instruction to the crowds in Matthew 23:3 to obey and do everything the teachers of the Law and the Pharisees tell them comes as a surprise. It is the only case in Matthew where the words of the Jewish leaders are seemingly portrayed in a positive light. If this portrayal indeed is positive, it seems to stand in tension with how Matthew construes these leaders and their teachings in the rest of the gospel (e.g. Mt 5:20; 15:3–6, 15:14; 16:11–12). Jesus’ positive remark furthermore seemingly stands in contrast with Matthew 28:20, where Jesus claims all authority to himself and instructs his disciples to teach all the nations to obey everything he has commanded them. The question therefore arises as to how this seemingly positive reference of Jesus, which apparently stands in contrast with Jesus’ criticism in the rest of the gospel, should be interpreted. In answering this question, an intra-textual approach is followed.